Neurocognition Function of Patients With Bipolar Depression, Unipolar Depression, and Depression With Bipolarity - Lu, Zhe; Wang, Yingtan; Xun, Guanglei (Frontiers in Psychiatry, 2021)
There is much evidence that shows that some DSM-5-defined unipolar depression (UD) with bipolarity manifest bipolar diathesis. Little is known about the cognitive profiles of patients with depression with bipolarity (DWB). The study aimed to investigate the differences in cognitive profiles between patients with bipolar depression (BD), major depressive disorder (namely unipolar depression, UD), and depression with bipolarity (DWB). Drug-naïve/free patients with BD, UD, DWB, and healthy controls (HC) were recruited (30 cases in each group). Cognition function was evaluated by THINC-it (THINC-intelligent tool), Wisconsin Card Sorting Test (WCST), and Continue Performance Test (CPT).For THINC-it, the differences of the Z-scores in both objective and subjective parts between DWB and BD were not significant, Z-scores of the BD group were lower than the UD group. For WCST, differences in the number of responses, categories completed, trails to completed first category, perseverative responses and perseverative errors between BD group and DWB group were not significant. All the indices of WCST in DWB group were worse than UD group except for trails to completed first category and total number of response correct. For CPT, only leakage responses and false responses in 4-digital number of BD and DWB group more than UD group, and the difference between BD and DWB were not significant. Patients with DWB might perform differently from those with UD but similarly to those with BD in cognition impairment.